A Novel, Direct NO Donor Regulates Osteoblast and Osteoclast Functions and Increases Bone Mass in Ovariectomized Mice. (7th September 2016) - Kalyanaraman, Hema; Ramdani, Ghania; Joshua, Jisha; Schall, Nadine; Boss, Gerry R; Cory, Esther; Sah, Robert L; Casteel, Darren E; Pilz, Renate B
ABSTRACT: Most US Food and Drug Administration (FDA)‐approved treatments for osteoporosis target osteoclastic bone resorption. Only PTH derivatives improve bone formation, but they have drawbacks, and novel bone‐anabolic agents are needed. Nitrates, which generate NO, improved BMD in estrogen‐deficient rats and may improve bone formation markers and BMD in postmenopausal women. However, nitrates are limited by induction of oxidative stress and development of tolerance, and may increase cardiovascular mortality after long‐term use. Here we studied nitrosyl‐cobinamide (NO‐Cbi), a novel, direct NO‐releasing agent, in a mouse model of estrogen deficiency–induced osteoporosis. In murine primary osteoblasts, NO‐Cbi increased intracellular cGMP, Wnt/β‐catenin signaling, proliferation, and osteoblastic gene expression, and protected cells from apoptosis. Correspondingly, in intact and ovariectomized (OVX) female C57Bl/6 mice, NO‐Cbi increased serum cGMP concentrations, bone formation, and osteoblastic gene expression, and in OVX mice, it prevented osteocyte apoptosis. NO‐Cbi reduced osteoclasts in intact mice and prevented the known increase in osteoclasts in OVX mice, partially through a reduction in the RANKL/osteoprotegerin gene expression ratio, which regulates osteoclast differentiation, and partially through direct inhibition of osteoclast differentiation, observed in vitro in the presence of excess RANKL. The positive NO effects in osteoblasts were mediated by cGMP/protein kinase G (PKG), but some of the osteoclast‐inhibitory effects appeared to be cGMP‐independent. NO‐Cbi increased trabecular bone mass in both intact and OVX mice, consistent with its in vitro effects on osteoblasts and osteoclasts. NO‐Cbi is a novel direct NO‐releasing agent that, in contrast to nitrates, does not generate oxygen radicals, and combines anabolic and antiresorptive effects in bone, making it an excellent candidate for treating osteoporosis. © 2016 American Society for Bone and Mineral Research.